PENERAPAN KONSEP 4A PADA DESA WISATA KUBU GADANG KOTA PADANG PANJANG PROVINSI SUMATERA BARAT - Amalia Firez; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
A tourist village is a rural area that has the privilege of being a tourist destination. The tourist village is also a type of integration of the 4A concept, namely attractions, accessibility, additional facilities and services. The research method used in this research is a qualitative descriptive research method. This research describes a symptom based on the situation and observations that underlie the research or not about a symptom being studied. This research was conducted in the Kubu Gadang Tourism Village which is located in Padang Panjang City, West Sumatera Province. This study aims to determine the application of the 4A concept, and the obstacles in implementing the 4A concept in the Kubu Gadang Tourism Village. The application of the 4A concept to the Kubu Gadang Tourism Village has been carried out well and in accordance with existing regulations. Constraints from implementing the 4A concept, namely tourism product components that have not run optimally such as facilities in the form of no parking space, lack of toilets, far prayer rooms. Attractions must be booked in advance, and there is still a lack of musical instruments to be used for activities. Keywords : Kubu Gadang Tourism Village, Concept 4A